Gamification Design Predicaments for E-learning - Palmquist, Adam; Munkvold, Robin; Goethe, Ole (HCI in Games: Serious and Immersive Games, 2021)
We introduce how gambling techniques slurred as gamification can be abusive and how adapting it for HCI can lay a practical basis for unethical designs, both in the commercial and applied research sectors. Based on the original notion of game theory, we argue that these techniques can be pervasive in our everyday socio-technical ecosystem. The digital technology industry’s commercial underpinnings frequently promote irrational user-behavior and using these design techniques in educational technology could foster negative user learning behaviors. Given the complexity of these concepts’ legal issues, it is not always easy to ensure that one does not cross the line. This study presents four gamification design predicaments that demand attention when designing gamification in (e)learning. The research has both theory and practical implications.